PERADABAN ILMU ANDALUSIA : MASA PUNCAK DAN KEHANCURANNYA - iwan setiawan (IAIN Syekh Nurjati Cirebon, 2021)
Andalusia is face from bright Muslim civilization in west region. If the researchers identified Islam as pasrt of eastern civilization, it should be correction. Andalusia as a part of history of Muslim civilization will show that the part of Islam in the west has a great gold of Islam history. This is the important of reading the past time for looking the future. The Andalusia Muslim civilization is not popular Muslim civilization in Baghdad era Al-Makmum for Muslim. It is needed as make writing toward the role of Muslim scientist in Andalusia. Between Baghdad in the east and Andalusia in the west constitutes the authentic prove of Muslim scientist civilization in the past time. A part of the past time, the writing about history of Andalusia knowledge is not just for romantic. Andalusia is a part of Muslim knowledge civilization tradition needs to be studied again. Studying on the making of knowledge civilization in Andalusia and study on the reasons decrease of the knowledge civilization in Andalusia. Keywords: Andalusia, Knowledge Civilization, Peak and Destruction